LO090: Introduction of a formalized RUSH (Rapid Ultrasound in Shock) protocol in emergency medicine residency ultrasound training. (2nd June 2016) - Hrymak, C.; Pham, C.
Abstract : Introduction / Innovation Concept: Expanding point of care ultrasound education in emergency medicine (EM) programs is a necessary part of curriculum development. Our objective was to integrate core and advanced applications for point of care ultrasound in caring for critically ill patients with undifferentiated shock. We chose to develop and implement an educational module using the systematic approach of the RUSH Exam for EM residents in our institution.Methods: After review of the literature in point-of-care ultrasound, a module was designed. An educational proposal outlining the RUSH Exam training within the -EM and CCFP-EM curricula was submitted to and accepted by the residency training committee. The objectives and goals were outlined in accordance with CanMEDS roles, and the ultrasound director provided supervision for the project.Curriculum, Tool, or Material: An 8-hour educational module was implemented between October 7 and November 18, 2014. All residents received formal training on the core applications in FAST and aortic scans prior to implementation. The following components of the RUSH Exam were included: two hours of didactic teaching with video clips on advanced cardiac, IVC, DVT, and pulmonary assessment; three hours of hands-on practice on standardized patients performed in the simulation lab to practice image acquisition and interpretation; one hour of didactic teaching on the overall approach to a patient with undifferentiated shock using the RUSH Exam; and two hours of hands-on RUSH Exam practice. A corresponding research project integrating a SonoSim Livescan training platform, a simulation-based testing device, demonstrated improvement in resident performance, subjective comfort with imaging patients in shock and making clinical decisions based on the findings.Conclusion: This 8-hour RUSH Exam educational module combined theoretical learning and hands-on practice for trainees. This module significantly broadened the scope of ultrasound training in our curriculum by providing the necessary skills in approaching patients in shock in a systematic fashion. Future direction will include ongoing education in this area and expansion as appropriate.